Polypropylene composite material and preparation method thereof
Through reasonable proportioning and modification of the materials, polypropylene composite materials with high tensile strength, flame retardant properties and low molding shrinkage were prepared, which solved the problems of poor fire resistance and insufficient toughness of existing polypropylene materials, and expanded its application scope.
Patent Information
- Application Number
- CN202510114113.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-18
AI Technical Summary
The existing polypropylene materials have poor fire resistance and insufficient toughness, which leads to combustible and injection molding defects such as shrinkage marks and warping, which limits their application.
Through reasonable proportions, polypropylene, maleic anhydride grafted polypropylene, composite modified paraffinite and other materials are mixed and melted, and the twin screw extruder is used for melt extrusion and granulation. The obtained polypropylene composite material has good tensile strength, flame retardant properties and low molding shrinkage.
The prepared polypropylene composite material is not prone to warping or deformation, and has a wider application prospect. At the same time, it improves the mechanical properties and flame retardant properties of the material and reduces the molding shrinkage rate.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polypropylene composite materials, and in particular to a polypropylene composite material and a preparation method thereof. Background Art
[0002] Polypropylene (PP) is a thermoplastic resin with a highly crystalline structure. Its odorless, non-toxic and lightweight properties make it popular in many fields. As an important engineering plastic, PP has been widely used in the automotive industry, home appliances, packaging, building materials, furniture manufacturing and other industries due to its good physical and mechanical properties, low cost and excellent processability.
[0003] However, existing polypropylene materials still have obvious defects in certain properties and are in urgent need of improvement and enhancement. First, since the limiting oxygen index of polypropylene materials is as low as 17-18%, the fire resistance is poor. Once ignited, it is extremely easy to burn, quickly releases a large amount of heat, and is accompanied by serious molten dripping, which can easily ignite other combustibles and cause large-scale fires. Secondly, the toughness of polypropylene materials is insufficient. Polypropylene materials are composed of polypropylene molecular chains, which are relatively soft and regular. When subjected to tensile external forces, the molecular chains are prone to slippage, causing the material to deform significantly under lower tension. The existing technology usually modifies polypropylene by adding flame retardants, inorganic or organic fillers, etc., to achieve the purpose of improving the flame retardancy and toughness of polypropylene materials.
[0004] CN119119637A discloses a toughened scratch-resistant polypropylene composite material, which is made of the following ingredients: polypropylene resin, maleic anhydride grafted polyethylene, modified nano silicon carbide, organosilane coupling agent, inorganic filler, antioxidant, stearic acid, elastomer, and nano zinc oxide. The polypropylene composite material prepared by the invention not only has excellent mechanical properties, but also has excellent scratch resistance. However, the polypropylene composite material has poor flame retardancy, and the inorganic filler is nano calcium carbonate, which has poor compatibility with the polypropylene resin, which is not conducive to the overall performance of the polypropylene composite material.
[0005] CN118812989A discloses a polypropylene composite material and its preparation method and application. The polypropylene composite material of the invention includes the following components by mass: 70-80 parts of polypropylene; 0.3-0.8 parts of antioxidant; 1-5 parts of hypophosphite flame retardant; 0.2-0.6 parts of bromine flame retardant; 5-16 parts of talcum powder loaded with flame retardant synergist; 5-11 parts of processing aid. The polypropylene composite material obtained by the invention is a low-halogen flame-retardant polypropylene material, which can stabilize the melt index and melt strength during high-temperature processing and ensure the stable extrusion of thick plates. However, since polypropylene is a crystalline material, the shrinkage rate is relatively large. The shrinkage rate of pure polypropylene is 1.4-1.7%. Even after adding talcum powder and other fillers for modification, its shrinkage rate is generally more than 0.9%. During injection molding, it is easy to produce injection defects such as shrinkage marks and warping, which limits its application. Summary of the invention
[0006] In view of the above-mentioned defects of the prior art, the present invention provides a polypropylene composite material and a preparation method thereof. The polypropylene composite material prepared by the present invention not only has good tensile strength and flame retardant properties, but also has a low molding shrinkage rate, so that the prepared polypropylene composite material is not prone to warping and deformation, and can be applied to a wider range of fields.
[0007] To achieve the above object, the present invention provides a method for preparing a polypropylene composite material, comprising the following steps:
[0008] (1) Add polypropylene, maleic anhydride grafted polypropylene, filler, plasticizer, lubricant, anti-aging agent, and glass fiber into a mixer, stir and mix at a speed of 300-800 rpm for 20-60 minutes, and discharge to obtain a premix;
[0009] (2) The premix obtained in step (1) is put into a twin-screw extruder, the speed of the extruder is set to 400-700 rpm, the melting temperature is set to 190-210° C., and melt extrusion granulation is performed to obtain a polypropylene composite material.
[0010] Preferably, the weight ratio of each raw material component includes:
[0011] 65-85 parts of polypropylene, 5-15 parts of maleic anhydride grafted polypropylene, 5-12 parts of filler, 1-3 parts of plasticizer, 0.5-1.5 parts of lubricant, 0.5-2 parts of anti-aging agent, and 1-5 parts of glass fiber.
[0012] Preferably, the plasticizer is selected from one or more of dibutyl phthalate, dioctyl phthalate, and diisodecyl phthalate.
[0013] Preferably, the lubricant is one or more of stearic acid, paraffin, zinc stearate, and ethylene bisstearamide.
[0014] Preferably, the anti-aging agent is compounded by antioxidant 1010, antioxidant 168 and ultraviolet absorber UV-531 in a mass ratio of 1-2:1-2:0.5-1.
[0015] Preferably, the filler is a composite modified palygorskite, and the preparation method thereof comprises the following steps, calculated by weight:
[0016] S1. Mix 3-5 parts of palygorskite with 30-35 parts of 1-2 mol / L hydrochloric acid aqueous solution, disperse them ultrasonically at an ultrasonic frequency of 20-50 kHz for 20-40 min, and then place them at 78-82° C. for mixing and reacting for 0.5-2 h; then wash with water until neutral, centrifuge, collect the precipitate, and vacuum dry the precipitate at 40-50° C. for 22-25 h to obtain acid-activated palygorskite;
[0017] S2, adding 2.5-3.5 parts of the acid-activated palygorskite obtained in the above step S1 to 12-18 parts of water, stirring evenly to obtain a dispersion, adding 2.5-3.5 parts of a modifier, 0.5-1.2 parts of a silane coupling agent KH-560 and 18-25 parts of ethanol to the dispersion, mixing and stirring at 200-400rpm and 55-65°C for 2-4h; centrifuging, collecting a precipitate, washing the precipitate with water for 2-3 times, and vacuum drying at 55-65°C for 2-4h to obtain a composite modified palygorskite.
[0018] Palygorskite itself has a special crystal structure, and its crystals are fibrous or rod-shaped. This form can exist as a reinforcing phase in polypropylene resin. When the composite material is subjected to a tensile external force, the fibrous palygorskite can be arranged along the tensile direction, and bear part of the external force like a bridge, effectively transferring the stress from the polypropylene matrix to the palygorskite, which is conducive to improving the mechanical properties of the polypropylene matrix. However, since palygorskite has a large specific surface area and correspondingly has a high surface energy, it is prone to agglomeration, and has poor compatibility with polypropylene resin, which affects its reinforcing effect. In order to enable palygorskite to play its reinforcing role more effectively, the present invention modifies palygorskite to obtain a composite modified palygorskite, which improves the compatibility between palygorskite and polypropylene.
[0019] In the preparation process of the composite modified palygorskite, the palygorskite is first activated with hydrochloric acid to obtain acid-activated palygorskite with a larger specific surface area and higher reactivity. Then the acid-activated palygorskite is mixed with the silane coupling agent KH-560 and the modifier for reaction. During the reaction, the organic functional groups in the molecular structure of the silane coupling agent KH-560 can react chemically with the hydroxyl groups on the surface of the acid-activated palygorskite to form chemical bonds, thereby modifying the surface of the acid-activated palygorskite, improving its surface activity and introducing epoxy groups; then the introduced epoxy groups can undergo a ring-opening reaction with the phosphorus hydroxyl groups of the phytic acid in the modifier to form a stable COP bond, thereby grafting the modifier to the surface of the palygorskite to obtain the composite modified palygorskite. The inventors have found that the introduction of the composite modified palygorskite in the preparation process of the polypropylene composite material of the present invention is not only conducive to improving the tensile strength and flame retardancy of the polypropylene composite material, but also conducive to reducing its molding shrinkage.
[0020] Further preferably, the method for preparing the modifier in step S2 comprises the following steps, in parts by weight:
[0021] Mix 3-4 parts of phytic acid, 2-3 parts of additives and 20-30 parts of water to obtain a mixed solution, place the mixed solution under 200-500rpm, 85-95℃ mixing and stirring for 15-30min, and then heat-reflect at 85-95℃ for 3-5h; after cooling, the reaction solution is concentrated by a rotary evaporator to obtain a solid product; and then the solid product is vacuum dried at 65-75℃ for 22-25h to obtain a modifier.
[0022] More preferably, the additive is selected from at least one of 2,4,6-triaminopyrimidine, 2,4-diamino-6-chloropyrimidine and 2-amino-4-hydroxy-6-methylpyrimidine.
[0023] In the preparation process of the above-mentioned modifier, phytic acid is mixed with at least one of the additives of the present invention, 2,4,6-triaminopyrimidine, 2,4-diamino-6-chloropyrimidine, and 2-amino-4-hydroxy-6-methylpyrimidine, under heating conditions, and the hydroxyl groups in the phytic acid can react with the amino groups in the additive structure to form ionic bonds, so that the additives are grafted onto the phytic acid to form a modifier.
[0024] The present invention also provides a polypropylene composite material, which is prepared by the above method.
[0025] Beneficial effects of the present invention:
[0026] 1. Compared with the prior art, the present invention mixes and melts polypropylene, maleic anhydride grafted polypropylene, filler, plasticizer, lubricant, anti-aging agent, and glass fiber in a reasonable proportion, and prepares a polypropylene composite material by extrusion and granulation. Polypropylene is selected as the matrix of the composite material to provide basic mechanical properties and processing properties for the material. At the same time, the introduction of maleic anhydride grafted polypropylene as a compatibilizer can significantly improve the compatibility between the filler and the glass fiber and the polypropylene matrix. Diisodecyl phthalate is selected as a plasticizer to reduce the melt viscosity of the polypropylene composite material and improve the processing properties of the material; zinc stearate plays a role in lubrication and demoulding, which is beneficial to improve the processing properties of the polypropylene composite material and helps to ensure the surface quality of the finished product. The present invention can effectively improve the aging resistance of the material and extend the service life of the material by compounding antioxidant 1010, antioxidant 168 and ultraviolet absorber UV-531 to form an anti-aging agent, so that it can maintain good performance during outdoor or long-term use. Glass fiber has high strength and modulus. When added to polypropylene composite materials, it can significantly improve the mechanical properties of the material and effectively increase the tensile strength and stiffness of the material.
[0027] 2. Compared with the prior art, the present invention prepares a modifier by mixing phytic acid with an additive containing an active nitrogen-containing group, and uses the modifier and silane coupling agent KH-560 to modify acid-activated palygorskite to prepare a composite modified palygorskite. The present invention introduces the prepared composite modified palygorskite as a filler into a polypropylene matrix to prepare a polypropylene composite material, which is beneficial to enhancing the tensile strength and flame retardant properties of the polypropylene composite material, while also reducing the molding shrinkage of the polypropylene composite material, and the transverse shrinkage and longitudinal shrinkage decreases tend to be consistent, and the difference between the two values is very small. The prepared polypropylene composite material is not prone to warping and deformation, and can be applied to a wider range of fields. DETAILED DESCRIPTION
[0028] Parameters for specific chemical substances used, sources.
[0029] Polypropylene, grade: K9928H, brand: Zhejiang Petrochemical;
[0030] Glass fiber: diameter: 10μm, short cut length 4.5mm, grade: 508A, brand: China Jushi;
[0031] Maleic anhydride grafted polypropylene, item number: PC-1, from Foshan Nanhai Bochen Polymer New Materials;
[0032] Palygorskite, mesh number: 325 mesh.
[0033] Embodiment 1:
[0034] A method for preparing a polypropylene composite material comprises the following steps:
[0035] (1) 82 parts by weight of polypropylene, 12 parts by weight of maleic anhydride grafted polypropylene, 10 parts by weight of composite modified palygorskite, 2 parts by weight of diisodecyl phthalate, 1.2 parts by weight of zinc stearate, 1.5 parts by weight of an anti-aging agent, and 4 parts by weight of glass fiber were added into a blender, stirred and mixed at a speed of 650 rpm for 35 minutes, and discharged to obtain a premix;
[0036] (2) The premix obtained in step (1) is put into a twin-screw extruder, the speed of the extruder is set to 500 rpm, the melting temperature is set to 200° C., and melt extrusion granulation is performed to obtain a polypropylene composite material.
[0037] The anti-aging agent is prepared by compounding antioxidant 1010, antioxidant 168 and ultraviolet absorber UV-531 in a mass ratio of 1.2:1.2:0.6.
[0038] The preparation method of the composite modified palygorskite comprises the following steps:
[0039] S1. Mix 4 parts by weight of palygorskite with 32 parts by weight of a 2 mol / L aqueous hydrochloric acid solution, disperse the mixture by ultrasonication at an ultrasonic frequency of 40 kHz for 30 min, and then place the mixture at 80° C. for mixing and reacting for 1 h; then wash the mixture with water until it is neutral, centrifuge it, collect the precipitate, and vacuum dry the precipitate at 45° C. for 24 h to obtain acid-activated palygorskite;
[0040] S2. Add 3 parts by weight of the acid-activated palygorskite obtained in the above step S1 to 15 parts by weight of water, stir evenly to obtain a dispersion, add 3 parts by weight of a modifier, 1 part by weight of a silane coupling agent KH-560 and 20 parts by weight of ethanol to the dispersion, mix and stir at 300 rpm and 60° C. for 3 hours; centrifuge, collect the precipitate, wash the precipitate with water 3 times, and vacuum dry it at 60° C. for 3 hours to obtain a composite modified palygorskite.
[0041] The preparation method of the modifier in step S2 comprises the following steps:
[0042] 3.5 parts by weight of phytic acid, 2.5 parts by weight of 2,4,6-triaminopyrimidine and 25 parts by weight of water are mixed to obtain a mixed solution, the mixed solution is placed under mixing and stirring at 300 rpm and 90° C. for 20 minutes, and then heated under reflux at 90° C. for 3.5 hours; after cooling, the reaction solution is concentrated by a rotary evaporator to obtain a solid product; and then the solid product is vacuum dried at 70° C. for 24 hours to obtain a modifier.
[0043] Embodiment 2:
[0044] A method for preparing a polypropylene composite material, which is different from Example 1 in that the method for preparing the composite modified palygorskite comprises the following steps:
[0045] S1. Mix 4 parts by weight of palygorskite with 32 parts by weight of a 2 mol / L aqueous hydrochloric acid solution, disperse the mixture by ultrasonication at an ultrasonic frequency of 40 kHz for 30 min, and then place the mixture at 80° C. for mixing and reacting for 1 h; then wash the mixture with water until it is neutral, centrifuge it, collect the precipitate, and vacuum dry the precipitate at 45° C. for 24 h to obtain acid-activated palygorskite;
[0046] S2. Add 3 parts by weight of the acid-activated palygorskite obtained in the above step S1 to 15 parts by weight of water, stir evenly to obtain a dispersion, add 3 parts by weight of a modifier, 1 part by weight of a silane coupling agent KH-560 and 20 parts by weight of ethanol to the dispersion, mix and stir at 300 rpm and 60° C. for 3 hours; centrifuge, collect the precipitate, wash the precipitate with water 3 times, and vacuum dry it at 60° C. for 3 hours to obtain a composite modified palygorskite.
[0047] The preparation method of the modifier in step S2 comprises the following steps:
[0048] 3.5 parts by weight of phytic acid, 2.5 parts by weight of 2,4-diamino-6-chloropyrimidine and 25 parts by weight of water are mixed to obtain a mixed solution, the mixed solution is placed under mixing and stirring at 300 rpm and 90° C. for 20 minutes, and then heated under reflux at 90° C. for 3.5 hours; after cooling, the reaction solution is concentrated by a rotary evaporator to obtain a solid product; and then the solid product is vacuum dried at 70° C. for 24 hours to obtain a modifier.
[0049] Embodiment 3:
[0050] A method for preparing a polypropylene composite material, which is different from Example 1 in that the method for preparing the composite modified palygorskite comprises the following steps:
[0051] S1. Mix 4 parts by weight of palygorskite with 32 parts by weight of a 2 mol / L aqueous hydrochloric acid solution, disperse the mixture by ultrasonication at an ultrasonic frequency of 40 kHz for 30 min, and then place the mixture at 80° C. for mixing and reacting for 1 h; then wash the mixture with water until it is neutral, centrifuge it, collect the precipitate, and vacuum dry the precipitate at 45° C. for 24 h to obtain acid-activated palygorskite;
[0052] S2. Add 3 parts by weight of the acid-activated palygorskite obtained in the above step S1 to 15 parts by weight of water, stir evenly to obtain a dispersion, add 3 parts by weight of a modifier, 1 part by weight of a silane coupling agent KH-560 and 20 parts by weight of ethanol to the dispersion, mix and stir at 300 rpm and 60° C. for 3 hours; centrifuge, collect the precipitate, wash the precipitate with water 3 times, and vacuum dry it at 60° C. for 3 hours to obtain a composite modified palygorskite.
[0053] The preparation method of the modifier in step S2 comprises the following steps:
[0054] 3.5 parts by weight of phytic acid, 2.5 parts by weight of 2-amino-4-hydroxy-6-methylpyrimidine and 25 parts by weight of water are mixed to obtain a mixed solution, the mixed solution is placed under mixing and stirring at 300 rpm and 90° C. for 20 minutes, and then heated under reflux at 90° C. for 3.5 hours; after cooling, the reaction solution is concentrated by a rotary evaporator to obtain a solid product; and then the solid product is vacuum dried at 70° C. for 24 hours to obtain a modifier.
[0055] Comparative Example 1:
[0056] A method for preparing a polypropylene composite material, which is different from Example 1 in that the method for preparing the composite modified palygorskite comprises the following steps:
[0057] S1. Mix 4 parts by weight of palygorskite with 32 parts by weight of a 2 mol / L aqueous hydrochloric acid solution, disperse the mixture by ultrasonication at an ultrasonic frequency of 40 kHz for 30 min, and then place the mixture at 80° C. for mixing and reacting for 1 h; then wash the mixture with water until it is neutral, centrifuge it, collect the precipitate, and vacuum dry the precipitate at 45° C. for 24 h to obtain acid-activated palygorskite;
[0058] S2. Add 3 parts by weight of the acid-activated palygorskite obtained in the above step S1 to 15 parts by weight of water, stir evenly to obtain a dispersion, add 3 parts by weight of a modifier, 1 part by weight of a silane coupling agent KH-560 and 20 parts by weight of ethanol to the dispersion, mix and stir at 300 rpm and 60° C. for 3 hours; centrifuge, collect the precipitate, wash the precipitate with water 3 times, and vacuum dry it at 60° C. for 3 hours to obtain a composite modified palygorskite.
[0059] The preparation method of the modifier in step S2 comprises the following steps:
[0060] 3.5 parts by weight of phytic acid, 2.5 parts by weight of cytosine and 25 parts by weight of water are mixed to obtain a mixed solution, the mixed solution is placed under mixing and stirring at 300 rpm and 90° C. for 20 minutes, and then heated under reflux at 90° C. for 3.5 hours; after cooling, the reaction solution is concentrated by a rotary evaporator to obtain a solid product; and then the solid product is vacuum dried at 70° C. for 24 hours to obtain a modifier.
[0061] Comparative Example 2:
[0062] A method for preparing a polypropylene composite material, which is different from Example 1 in that the method for preparing the composite modified palygorskite comprises the following steps:
[0063] S1. Mix 4 parts by weight of palygorskite with 32 parts by weight of a 2 mol / L aqueous hydrochloric acid solution, disperse the mixture by ultrasonication at an ultrasonic frequency of 40 kHz for 30 min, and then place the mixture at 80° C. for mixing and reacting for 1 h; then wash the mixture with water until it is neutral, centrifuge it, collect the precipitate, and vacuum dry the precipitate at 45° C. for 24 h to obtain acid-activated palygorskite;
[0064] S2. Add 3 parts by weight of the acid-activated palygorskite obtained in the above step S1 to 15 parts by weight of water, stir evenly to obtain a dispersion, add 3 parts by weight of a modifier, 1 part by weight of a silane coupling agent KH-550 and 20 parts by weight of ethanol to the dispersion, mix and stir at 300 rpm and 60° C. for 3 hours; centrifuge, collect the precipitate, wash the precipitate with water 3 times, and vacuum dry it at 60° C. for 3 hours to obtain a composite modified palygorskite.
[0065] The preparation method of the modifier in step S2 is consistent with that in Example 1.
[0066] Comparative Example 3:
[0067] A method for preparing a polypropylene composite material comprises the following steps:
[0068] (1) 82 parts by weight of polypropylene, 12 parts by weight of maleic anhydride grafted polypropylene, 10 parts by weight of modified palygorskite, 2 parts by weight of diisodecyl phthalate, 1.2 parts by weight of zinc stearate, 1.5 parts by weight of an anti-aging agent, and 4 parts by weight of glass fiber were added into a mixer, stirred and mixed at a speed of 650 rpm for 35 minutes, and discharged to obtain a premix;
[0069] (2) The premix obtained in step (1) is put into a twin-screw extruder, the speed of the extruder is set to 500 rpm, the melting temperature is set to 200° C., and melt extrusion granulation is performed to obtain a polypropylene composite material.
[0070] The anti-aging agent is prepared by compounding antioxidant 1010, antioxidant 168 and ultraviolet absorber UV-531 in a mass ratio of 1.2:1.2:0.6.
[0071] The preparation method of the modified palygorskite comprises the following steps:
[0072] S1. Mix 4 parts by weight of palygorskite with 32 parts by weight of a 2 mol / L aqueous hydrochloric acid solution, disperse the mixture by ultrasonication at an ultrasonic frequency of 40 kHz for 30 min, and then place the mixture at 80° C. for mixing and reacting for 1 h; then wash the mixture with water until it is neutral, centrifuge it, collect the precipitate, and vacuum dry the precipitate at 45° C. for 24 h to obtain acid-activated palygorskite;
[0073] S2. Add 3 parts by weight of the acid-activated palygorskite obtained in the above step S1 to 15 parts by weight of water, stir evenly to obtain a dispersion, add 1 part by weight of silane coupling agent KH-560 and 20 parts by weight of ethanol to the dispersion, mix and stir at 300 rpm and 60° C. for 3 hours; centrifuge, collect the precipitate, wash the precipitate with water 3 times, and vacuum dry it at 60° C. for 3 hours to obtain modified palygorskite.
[0074] Comparative Example 4:
[0075] A method for preparing a polypropylene composite material comprises the following steps:
[0076] (1) 82 parts by weight of polypropylene, 12 parts by weight of maleic anhydride grafted polypropylene, 10 parts by weight of palygorskite, 2 parts by weight of diisodecyl phthalate, 1.2 parts by weight of zinc stearate, 1.5 parts by weight of an anti-aging agent, and 4 parts by weight of glass fiber were added into a blender, stirred and mixed at a speed of 650 rpm for 35 minutes, and discharged to obtain a premix;
[0077] (2) The premix obtained in step (1) is put into a twin-screw extruder, the speed of the extruder is set to 500 rpm, the melting temperature is set to 200° C., and melt extrusion granulation is performed to obtain a polypropylene composite material.
[0078] The anti-aging agent is prepared by compounding antioxidant 1010, antioxidant 168 and ultraviolet absorber UV-531 in a mass ratio of 1.2:1.2:0.6.
[0079] Test Example 1:
[0080] Performance Test:
[0081] Tensile strength: The polypropylene composite materials prepared in Examples 1-3 of the present invention and Comparative Examples 1-4 were respectively made into samples that met the test specifications, and then the tensile strength of the samples was tested with reference to the standard "GB / T 1040.1-2018 Determination of tensile properties of plastics Part 1: General Principles";
[0082] Flame retardant property: The polypropylene composite materials prepared in Examples 1-3 of the present invention and Comparative Examples 1-4 were respectively processed into injection molded specimens in a vertical injection molding machine for flame retardant property test; the limiting oxygen index was tested with reference to GB / T 2406.2-2009 Determination of combustion behavior of plastics by oxygen index method Part 2: Room temperature test, and the sample size was 80 mm×10 mm×4 mm; the vertical combustion test was tested with reference to GB / T 2408-2021 Determination of combustion performance of plastics by horizontal and vertical methods, and the sample size was 120 mm×12.5 mm×3.0 mm, and each group of samples was tested five times in parallel to take the average value; generally speaking, the vertical combustion test results are evaluated by vertical combustion levels V-0, V-1, and V-2, among which V-0 level has the best effect, and V-1 and V-2 have decreasing effects in descending order; the flame retardant properties of the polypropylene composite materials prepared in each embodiment and comparative example were evaluated according to the test results;
[0083] The test results are averaged, and the specific results are shown in Table 1 below:
[0084] Table 1:
[0085] ;
[0086] As shown in Table 1, compared with Comparative Example 3 in which the filler is modified palygorskite and Comparative Example 4 in which the filler is palygorskite, the tensile strength and limiting oxygen index of Examples 1-3 and Comparative Example 1-2 in which the filler is composite modified palygorskite are significantly higher than those of Comparative Example 3-4, and the vertical combustion level reaches V-0, indicating that composite modified palygorskite is more conducive to improving the tensile strength and flame retardant properties of polypropylene composite materials than selecting modified palygorskite or palygorskite as filler. The reason for this may be that the silane coupling agent KH-560 introduced on the surface of the composite modified palygorskite and the functional groups in the modifier structure can interact with the polypropylene molecular chain through physical adsorption or chemical bonding, thereby enhancing the interfacial bonding strength between palygorskite and polypropylene, avoiding agglomeration, and improving its compatibility with polypropylene. Good dispersibility and compatibility ensure that palygorskite is evenly distributed in the polypropylene matrix, avoiding agglomeration, thereby more effectively exerting the reinforcing effect of palygorskite, which is beneficial to improving the tensile strength of polypropylene composites. When the polypropylene composite is heated and burned, palygorskite can form a physical barrier layer on the surface of the material, which can prevent the molten material of the polypropylene resin from dripping, thereby reducing the spread of the flame. In addition, the phosphate groups contained in the phytic acid grafted with the composite modified palygorskite may catalyze the dehydration and carbonization reaction of polypropylene during the combustion process, thereby promoting the formation of a carbon layer when the polypropylene resin is burned, which can form an effective flame retardant mechanism. At the same time, during the combustion process of the modifier grafted with the composite modified palygorskite, the amino groups in the structures of 2,4,6-triaminopyrimidine, 2,4-diamino-6-chloropyrimidine, and 2-amino-4-hydroxy-6-methylpyrimidine in the modifier may decompose to produce non-combustible gases such as ammonia, reduce the concentration of oxygen and combustible substances, have a significant inhibitory effect on combustion, and enhance the flame retardant properties of polypropylene composites.
[0087] It can be found from Examples 1-3 and Comparative Examples 1-2 that the tensile strength and limiting oxygen index of Examples 1-3 are higher than those of Comparative Examples 1-2, wherein the tensile strength and limiting oxygen index of Example 1 are the highest, with a tensile strength of 62.4 MPa and a limiting oxygen index of 33.8%. The reason for this analysis may be that in the process of preparing the composite modified palygorskite, the silane coupling agent KH-560 used in Examples 1-3 and Comparative Example 1 contains an epoxy group, which can react with the phosphorus hydroxyl group of phytic acid in the modifier to form a stable COP bond. The COP bond is a covalent bond, which has a high bond energy and is relatively stable under general chemical environments and physical conditions. The formation of this chemical bond enables the modifier to be firmly grafted to the palygorskite surface, and is not easily affected by external factors and falls off, thereby firmly grafting the modifier to the palygorskite surface. Comparative Example 2 uses the silane coupling agent KH-550, which reacts with the hydroxyl group in the modifier through its amino group, so that the modifier is deposited on the palygorskite surface. The bond formed between the amino group and the hydroxyl group may be a hydrogen bond or a relatively weak covalent bond such as an amide bond. The bond energy of the hydrogen bond is relatively low, and the stability is not as good as that of the COP bond. When subjected to external force or chemical environment changes, it is more likely to break, causing the modifier to fall off the surface of the palygorskite. Therefore, the improvement effect of the composite modified palygorskite in Comparative Example 2 on the tensile strength and flame retardant properties of the polypropylene composite material is not as good as that of Examples 1-3 and Comparative Example 1.
[0088] Comparing Examples 1-3 and Comparative Example 1, compared with the selection of cytosine and phytic acid mixed to form a modifier in Comparative Example 1, Examples 1-3 respectively use 2,4,6-triaminopyrimidine, 2,4-diamino-6-chloropyrimidine, 2-amino-4-hydroxy-6-methylpyrimidine and phytic acid to form a modifier; 2,4,6-triaminopyrimidine and 2,4-diamino-6-chloropyrimidine contain more active nitrogen-containing groups such as amino groups than cytosine, and can produce more non-flammable gases, so the flame retardant effect is better. The hydroxyl group in 2-amino-4-hydroxy-6-methylpyrimidine makes it have better reactivity with phytic acid, and the synergistic flame retardant effect with phytic acid is better than cytosine. Comparing Examples 1-3, the number of nitrogen-containing groups in 2,4,6-triaminopyrimidine used in Example 1 is the largest, and more non-flammable gases can be produced during the combustion process. Therefore, in terms of flame retardancy, the advantage of Example 1 is the most obvious.
[0089] Test Example 2:
[0090] Molding shrinkage test:
[0091] The polypropylene composite materials prepared in Examples 1-3 of the present invention and Comparative Examples 1-4 were respectively injection molded in a square plate mold of 80 mm×220 mm×2 mm, and then allowed to stand for 48 hours at 23° C. and 50% relative humidity. The difference between the size of the square plate after molding and the size of the mold was measured, and the molding shrinkage (transverse shrinkage and longitudinal shrinkage) was calculated, wherein the transverse shrinkage and longitudinal shrinkage were calculated according to the following formula:
[0092] Transverse shrinkage (%) = (A1-A0) / A0×100%;
[0093] In the above formula, A1 is the length after forming, and A0 is the length of the mold;
[0094] Longitudinal shrinkage (%) = (B1-B0) / B0×100%;
[0095] In the above formula, B1 is the width after forming, and B0 is the width of the mold;
[0096] The test results are averaged, and the specific results are shown in Table 2 below:
[0097] Table 2:
[0098] ;
[0099] As shown in Table 2, by comparing Examples 1-3 and Comparative Examples 1-4, it is found that the transverse shrinkage and longitudinal shrinkage of Examples 1-3 and Comparative Examples 1-2, in which the filler is composite modified palygorskite, are significantly lower than those of Comparative Example 3 in which the filler is modified palygorskite and Comparative Example 4 in which the filler is palygorskite, and the difference between the transverse shrinkage and longitudinal shrinkage is very small, indicating that compared with selecting modified palygorskite or palygorskite as a filler, composite modified palygorskite as a filler is more conducive to reducing the shrinkage of polypropylene composite materials. The reason for the analysis may be that palygorskite itself has a special crystal structure, and its crystals are fibrous or rod-shaped, resulting in relatively small size changes when the temperature changes, and has a lower thermal expansion coefficient. Polypropylene, as a thermoplastic material, has a relatively high thermal expansion coefficient. The present invention introduces composite modified palygorskite into a polypropylene composite material. When the temperature changes, the composite modified palygorskite uniformly dispersed in the polypropylene group acts as an "anchor point", and its fibrous or rod-like form will construct a stable physical network structure, similar to a "skeleton". Because the composite modified palygorskite itself will not shrink significantly in volume like polypropylene during the cooling process, the free shrinkage of the polypropylene resin is limited, and the shrinkage of the polypropylene is restrained, thereby reducing the shrinkage rate of the polypropylene composite material. Compared with the modified palygorskite and the unmodified palygorskite, the palygorskite after the silane coupling agent KH-560 and the modifier are composite-modified with the polypropylene to form a good interface bond, and the interaction is enhanced. Therefore, the polypropylene shrinkage needs to overcome the stronger restriction from the composite modified palygorskite, so that the overall shrinkage of the composite material is suppressed, and the shrinkage rate reduction effect is more obvious.
[0100] By comparing Examples 1-3 and Comparative Examples 1-2, it is found that the shrinkage of Examples 1-3 is lower than that of Comparative Examples 1-2, among which Example 1 has the lowest shrinkage, with a transverse shrinkage of 0.33% and a longitudinal shrinkage of 0.41%. The reason for this may be that compared with Comparative Example 2, which uses silane coupling agent KH-550 to modify palygorskite, Examples 1-3 and Comparative Example 1 use silane coupling agent KH-560 to modify palygorskite in the composite modified palygorskite, and the prepared composite modified palygorskite is more stable and not easily affected by external factors such as temperature changes, so the shrinkage of the polypropylene composite material is better reduced.
[0101] Comparing Examples 1-3 and Comparative Example 1, 2,4,6-triaminopyrimidine, 2,4-diamino-6-chloropyrimidine, and 2-amino-4-hydroxy-6-methylpyrimidine are used in Examples 1-3, which have more active functional groups such as amino and hydroxyl groups compared to cytosine in Comparative Example 1. After being mixed with phytic acid to form a modifier, these active functional groups can have a more positive effect on the interfacial interaction between palygorskite and polypropylene. Therefore, Examples 1-3 have a more obvious effect on reducing shrinkage. Among Examples 1-3, 2,4,6-triaminopyrimidine has the most active functional groups in Example 1, which may have more advantages in forming a physical network structure, and works together with phytic acid to make the physical network structure formed by palygorskite in the polypropylene matrix more stable. Therefore, Example 1 has the most obvious advantage in reducing the shrinkage of the polypropylene composite material.
Claims
1. A method for preparing a polypropylene composite material, characterized in that: The following steps are involved: (1) Add polypropylene, maleic anhydride grafted polypropylene, filler, plasticizer, lubricant, anti-aging agent, and glass fiber into a mixer, stir and mix at a speed of 300-800 rpm for 20-60 minutes, and discharge to obtain a premix; (2) The premix obtained in step (1) is put into a twin-screw extruder, the speed of the extruder is set to 400-700 rpm, the melting temperature is set to 190-210° C., and melt extrusion granulation is performed to obtain a polypropylene composite material.
2. The method for preparing the polypropylene composite material according to claim 1, characterized in that: The weight proportions of the raw material components include: 65-85 parts of polypropylene, 5-15 parts of maleic anhydride grafted polypropylene, 5-12 parts of filler, 1-3 parts of plasticizer, 0.5-1.5 parts of lubricant, 0.5-2 parts of anti-aging agent, and 1-5 parts of glass fiber.
3. The method for preparing the polypropylene composite material according to claim 1 or 2, characterized in that: The plasticizer is selected from one or more of dibutyl phthalate, dioctyl phthalate, and diisodecyl phthalate.
4. The method for preparing the polypropylene composite material according to claim 1 or 2, characterized in that: The lubricant is one or more of stearic acid, paraffin, zinc stearate, and ethylene bis stearamide.
5. The method for preparing the polypropylene composite material according to claim 1 or 2, characterized in that: The anti-aging agent is prepared by compounding antioxidant 1010, antioxidant 168 and ultraviolet absorber UV-531 in a mass ratio of 1-2:1-2:0.5-1.
6. The method for preparing the polypropylene composite material according to claim 1 or 2, characterized in that: The filler is a composite modified palygorskite, and the preparation method thereof comprises the following steps, calculated by weight: S1. Mix 3-5 parts of palygorskite with 30-35 parts of 1-2 mol / L aqueous hydrochloric acid solution, disperse by ultrasonic at an ultrasonic frequency of 20-50 kHz for 20-40 min, and then place at 78-82° C. for mixing and reaction for 0.5-2 h; Then, the mixture is washed with water until neutral, centrifuged, and the precipitate is collected and vacuum dried at 40-50° C. for 22-25 h to obtain acid-activated palygorskite; S2, adding 2.5-3.5 parts of the acid-activated palygorskite obtained in the above step S1 to 12-18 parts of water, stirring evenly to obtain a dispersion, adding 2.5-3.5 parts of a modifier, 0.5-1.2 parts of a silane coupling agent KH-560 and 18-25 parts of ethanol to the dispersion, mixing and stirring at 200-400rpm and 55-65°C for 2-4h; centrifuging, collecting a precipitate, washing the precipitate with water for 2-3 times, and vacuum drying at 55-65°C for 2-4h to obtain a composite modified palygorskite.
7. The method for preparing the polypropylene composite material according to claim 6, characterized in that: The preparation method of the modifier in step S2 comprises the following steps, calculated by weight: Mix 3-4 parts of phytic acid, 2-3 parts of additives and 20-30 parts of water to obtain a mixed solution, place the mixed solution under 200-500rpm, 85-95℃ mixing and stirring for 15-30min, and then heat-reflect at 85-95℃ for 3-5h; after cooling, the reaction solution is concentrated by a rotary evaporator to obtain a solid product; and then the solid product is vacuum dried at 65-75℃ for 22-25h to obtain a modifier.
8. The method for preparing the polypropylene composite material according to claim 7, characterized in that: The additive is selected from at least one of 2,4,6-triaminopyrimidine, 2,4-diamino-6-chloropyrimidine, and 2-amino-4-hydroxy-6-methylpyrimidine.
9. A polypropylene composite material, characterized in that: The method is prepared by any one of claims 1 to 8.
Citation Information
Patent Citations
Toughened scratch-resistant polypropylene composite material
CN119119637A
Cited By
Anti-aging PP plate and preparation method thereof
CN121182067A
Aging-resistant PP plate and preparation method thereof
CN121182067B